Rapid 3D Human Body Modeling and Skinning Animation Based on Single Kinect (Journal of Fiber Bioengineering and Informatics, 2015)
Dynamic geometries acquisition of human is one of the most popular topics in the fields of computervision and computer graphics. This paper presents the related techniques on rapidly generation of humanmodel sequences and makes skinning animation using single Kinect. In specified applied conditions, ithas good animation effects and interaction functions. As the comparatively low request on resolutionby animation, using the Kinect can greatly save human body animation production time and reduceproduction cost.
Keywords: Human Body; Rapid Modeling; Single Kinect; Skinning Animation